Proper Nutritional Care and Growth and development Stimulation for Premature Children - Masita, Bertri; Pratiwi, Dessy; Yuningrat, Nova (Ridwan Institute, 2024)
Premature children, or those born before 37 weeks of gestation, are at high risk of experiencing health problems and developmental delays. Proper nutritional care is essential to support their physical growth and cognitive development. Adequate nutrition can help overcome malnutrition that is often experienced by premature children, which can affect long-term health. In addition, growth and development stimulation through social interaction and physical activity also plays an important role in increasing the developmental potential of premature children. This study aims to explore the importance of proper nutritional care and growth and development stimulation in premature children. This study uses a qualitative research method. The data collection technique in this study was through literature studies. The data that has been collected was then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study showed that the care of premature infants should begin with the provision of appropriate nutrition. This nutrition comes from breast milk, however, to meet the nutritional needs of premature infants, especially those who are very premature and have very low birth weight, breast milk alone is insufficient, so special formulas such as FSMP premature are needed. In addition, optimal nutritional care needs to be balanced with proper growth and development stimulation. Stimulation in premature babies can be done through various methods, such as physical contact, sound, sight, and movement. The role of parents is very important in supporting children's development, so they need to get accurate information about the appropriate care and types of stimulation.